Designing a management tool to assess safety culture in the workplace - Rojas Castro, José Luis (2020)
The safety culture that prevails within an organization and the way in which the latter addresses and manages safety problems has a significant influence on the safety-related behavior of people in the workplace. For that reason, it is essential that every organization is able to identify and objectively evaluate the factors that influence safety culture. This research paper seeks to identify the factors that affect safety culture and establish a qualitative rating scale for each. Consequently, the appropriate knowledge of each of these factors suggests more objective, accurate and effective safety actions. The review of prior objective European research led to the development of a proprietary methodology in order to design a tool that is applicable to the local environment that currently lacks one. The end result achieved was a questionnaire addressed to the workforce, which evaluated 32 out of 43 identified indicators that have a potential impact on safety culture, including the description of five levels of development for each indicator. Finally, the design of the tool to assess safety culture was validated and the incidence of four factors in safety culture was confirmed: leadership in safety, effective communication, participation of personnel in the construction of safety and existence of a continuous learning culture, which were associated with 24 indicators.